Google Review Analysis of “Duta We Care” Excellent Service as a Featured Service at a Central General Hospital in Padang - Alfitri, Alfitri; Nindrea, Ricvan Dana; Setiawan, Adek; Yuniarti, Elsa (Kesmas, 2025)
Improving healthcare service quality required both technical and interpersonal enhancements through a personalized approach, as demonstrated by the “Duta We Care” program at a Central General Hospital in Padang. This study aimed to evaluate the program’s effectiveness by analyzing patient feedback from Google Reviews. A descriptive quantitative design examined 2,035 patient reviews from March 2013 to June 2024. Using NVivo 12 software, the data analysis generated word clouds. The results showed that 68.20% of reviews received a 5-star rating, 9.48% a 4-star rating, 4.35% a 3-star rating, 2.27% a 2-star rating, and 15.70% a 1-star rating. Words like “friendly,” “professional,” “fast,” and “good” frequently appeared, which highlighted patient appreciation for the program’s interpersonal aspects. The “Duta We Care” program successfully raised patient satisfaction, evident from the increased ratings from 3.8 to 4.6. It was determined that staff friendliness and professionalism played a key role in this improvement. However, complaints about waiting times and limited facilities suggested the need for further operational and infrastructural enhancements.